Stock Price, Return, and Abnormal Return Differences Before and After Stock Split In High and Low Profile Companies Listed On The Indonesian Stock Exchange - Abdul Manap; Riah Ukur Br Ginting; Zurlina Lubis; Nurhaifa Idris; Mustangin Mustangin (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
The purpose of this study is to see if there are differences in stock prices, stock returns, and abnormal returns before and after a stock split in high-profile and low-profile companies. This study's research period was 2020-2022. The research was analyzed quantitatively using a purposive sampling method. Based on the sampling criteria, 39 companies were selected as research samples. Kolmogorov Smirnov The normality test was performed using a single sample test. Following the normality test, the data was processed using the two-paired-sample difference test. If the data were normally distributed, the t-test (paired sample t-test) was used; otherwise, the Wilcoxon Signed Rank test was used. The results of hypothesis testing revealed that (1) there are differences in stock prices before and after a stock split in high-profile companies. (2) In low-profile companies, stock prices differ before and after the stock split. (3) There are differences in stock returns in high-profile companies before and after a stock split. (4) There is no difference in stock returns for low-profile companies before and after the stock split. (5) There is no difference in abnormal returns in high-profile companies before and after the stock split. (6) There is no difference in abnormal returns in low-profile companies before and after the stock split. (7) There are differences in stock prices following a stock split between high-profile and low-profile companies. (8) There is no difference in stock returns in high and low-profile companies before and after the stock split. (9) There is no difference in abnormal stock returns before and after a stock split at high and low-profile companies.